Tumor Cerebellopontine Angle - Wahyuliati, Tri (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2006)
For about 85% of tumors in the region of the cerebellopontine angle is acoustic neuroma, 10% are meningiomas and 5% are epidermoid tumor. An acoustic neuroma is a benign tumour that develops in the acoustic or auditory nerve. The acoustic neuroma starts from schwann cells which cover the acoustic nerve and is sometimes therefore called a schwannoma.Hearing loss is the most frequent symptom. Vertigo or spinning occurs in about 20 percent of persons with acoustic neuroma. Early diagnose by signs and symptoms detection is very important in acoustic neuroma treatment. Unfortunately, misdiagnose becomes the problem in this step. The optimal test for excluding an acoustic neuroma is MRI. If an MRI cannot be done, CT scan should be obtained.About more than a half of all acoustic neuromas are presently treated with surgery. The recurrence rate of the tumor is about 3% after surgery. Overall, the risk of death from acoustic neuroma surgery is about 0.5 to 2 percent. Unexpected post-operative complications occur in roughly 20percent with more complications occurring in elderly and infirm individuals and those with large tumors. Surgical treatment where the brain is exposed is nearly always performed by a team of surgeons, usually including a neurologist, a neurosurgeon and an anesthesiolgist. Pathology anatomist is needed to make definitif diagnose.Sekitar 85% tumor yang tumbuh di daerah sudut serebelo pontin adalah neuroma akustik, sekitar 10% adalah meningioma dan sekitar 5% adalah tumor epidermoid. Neuroma akustik adalah tumor jinak yang tumbuh pada nervus akustikus, yang berasal dari sel schwann yang meliputi nervus akustikus sehingga disebut juga schwanoma.Gangguan pendengaran merupakan gejala yang paling sering ditemukan. Vertigo atau rasa berputar dirasakan pada sekitar 20% penderita. Diagnosa dini melalui pengenalan tanda dan gejala sangat penting dalam penatalaksanaan neuroma akustik. Sayangnya, hal ini seringkah terabaikan atau teijadi misdiagnosis. Pemeriksaan yang optimal adalah menggunakan MRI, namun jika hal itu tidak bisa dilakukan maka CT scan sebaiknya dilakukan.Sekitar lebih dari setengah kasus neuroma akustik diterapi melalui pembedahan. Angka kekambuhan setelah pembedahan sekitar 3%. Risiko kematian saat operasi sekitar 0,5 - 2%. Komplikasi setelah operasi muncul pada sekitar 20% penderita, yang paling banyak pada penderita usia dewasa serta pada tumor yang besar. Terapi pembedahan pada otak melibatkan tim yang terdiri dari dokter ahli saraf, bedah saraf dan ahli anestesi. Ahli patologi anatomi berperan dalam menentukan diagnosa pasti.